neurogenetics - Graeber, Manuel B.; Ptacek, Louis J.; Auburger, Georg W.J.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Neurogenetics publishes findings that contribute to a better understanding of the genetic basis of normal and abnormal function of the nervous system. Neurogenetic disorders are the main focus of the journal. Neurogenetics therefore includes findings in humans and other organisms that help understand neurological disease mechanisms and publishes papers from many different fields such as biophysics, cell biology, human genetics, neuroanatomy, neurochemistry, neurology, neuropathology, neurosurgery and psychiatry. All papers submitted to Neurogenetics should be of sufficient immediate importance to justify urgent publication. They should present new scientific results. Data merely confirming previously published findings are not acceptable. Neurogenetics is published in hardcopy and online. It includes Review Articles, Original Articles, Short Communications and Letters to the Editors.
Keywords: Human genetics; Molecular biology; Neurosciences; Neurosciences; Human Genetics; Molecular Medicine